2015
DOI: 10.1002/jhet.2391
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Evaluation of Antibacterial Effects of a New Class of Piperazinylquinolone Derivatives

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Pentafluoropyridine derivatives and cyanuric chloride were used for the synthesis of new piperazinylquinolone derivatives. These reactions provided N-fluoropyridiyl and N-cyanoryl chloride piperazinylquinolone derivatives in good yields. Synthesized compounds were evaluated for their antibacterial activities. These compounds displayed good to excellent antibacterial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Another research study revealed that dimers of the same fluoroquinolones or two different fluoroquinolones linked by a linker at C‐7 exhibited highly promising antibacterial activity against tested bacterial strains . From the results, it is clear that derivatives with a bulky C‐7 side chain are more potent against efflux mutants .…”
Section: Recent Advances Of Quinolone Antibacterial Agentsmentioning
confidence: 99%
“…Another research study revealed that dimers of the same fluoroquinolones or two different fluoroquinolones linked by a linker at C‐7 exhibited highly promising antibacterial activity against tested bacterial strains . From the results, it is clear that derivatives with a bulky C‐7 side chain are more potent against efflux mutants .…”
Section: Recent Advances Of Quinolone Antibacterial Agentsmentioning
confidence: 99%
“…The hybrids displayed improved antibacterial properties in comparison with ciprofloxacin. Compounds 106a and 108a showed good-to-excellent anti-microbial activity in agar disc diffusion method as well as with the use of broth microdilution technique [189].
…”
Section: Other Modificationsmentioning
confidence: 99%
“…Perfluoropyridine, or PFPy, is one example of these fluorinated compounds that has been used for a wide variety of purposes, ranging from general synthetic reactions [ 12 , 13 ] to complex pharmaceuticals [ 14 , 15 , 16 ] and materials [ 17 , 18 , 19 ]. Although it can be prepared in house by employing the methods described below, PFPy is commercially available, and is considered to be an economically viable option in modern times.…”
Section: Introductionmentioning
confidence: 99%